Geoscience Australia's Geophysical Network: critical infrastructure and observed and derived data for earth monitoring and community safety. Issue 1 (1st December 2016) - Costelloe, Marina; Bugden, Craig; Bathgate, Jonathan; Wang, Liejun; Lewis, Andrew; Jones, Bill; Li, Yue; Butterfield, Adon; Becher, Saskia; Ruyssenaers, John; McLauchlan, Laurence; Burke, Patrick; et al.
Abstract : Geoscience Australia operates and maintains a state-of-the-art network of stations and sophisticated instrumentation that monitors natural and anthropogenic (human-made) hazards in Australia and around the globe through its Geophysical Networks. Key responsibilities are to: operate and maintain the Australian National Seismograph Network (ANSN) and Urban Monitoring (UM) networks; operate and maintain Australian Comprehensive Nuclear-Test-Ban Treaty (CTBT) seismic, hydro-acoustic and infrasound technologies, as part of Australia's commitment to support monitoring of worldwide nuclear testing; operate and maintain a national network of geomagnetic observatories which form part of a global observatory network; provide technical expertise and advice to Geoscience Australia projects, such as the National Geospatial Reference Systems, Hazard and Risk Infrastructure and Applications, Regional Development, Vulnerability, Resilience and Mitigation and the JATWS (Joint Australian Tsunami Warning System); and, provide technical and operational support for significant Australian earthquake events and aftershock deployment studies. Geophysical data archives are stored on-site and can be freely downloaded from GA or international data centres. Seismic data can be accessed at GA and Incorporated Research Institutions for Seismology (IRIS) and geomagnetic data at INTERMAGNET. Seismic data from Geoscience Australia's Geophysical Networks feeds into important hazard maps including the probabilistic national earthquake hazard map and the probabilistic Tsunami hazard map. Geomagnetic data feeds into the International Geomagnetic Reference Field and has been used to develop the first 3-D conductivity map of Australia.